2020
DOI: 10.1136/bmj.m1835
|View full text |Cite
|
Sign up to set email alerts
|

Use of all cause mortality to quantify the consequences of covid-19 in Nembro, Lombardy: descriptive study

Abstract: OBJECTIVE To quantify the impact of coronavirus disease 2019 (covid-19) on all cause mortality in Nembro, an Italian city severely affected by the covid-19 pandemic. DESIGNDescriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
2
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 12 publications
6
59
2
2
Order By: Relevance
“…The clinical characteristics and clinical course of COVID-19 patients hospitalised in Lyon were similar to those reported in California [6], New York City [9], and Italy [5,7,8], which supports the generalisability of the proposed prediction tool. As reported in the analysis published byWynants et al [10], the most frequently reported diagnostic and prognostic predictors of covid-19 are age, body temperature, lymphocyte count and lung imaging characteristics.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The clinical characteristics and clinical course of COVID-19 patients hospitalised in Lyon were similar to those reported in California [6], New York City [9], and Italy [5,7,8], which supports the generalisability of the proposed prediction tool. As reported in the analysis published byWynants et al [10], the most frequently reported diagnostic and prognostic predictors of covid-19 are age, body temperature, lymphocyte count and lung imaging characteristics.…”
Section: Discussionsupporting
confidence: 76%
“…The most frequently reported diagnostic and prognostic predictors of COVID-19 are age, body temperature, lymphocyte count, and lung imaging characteristics. Flu-like symptoms and neutrophil counts are frequently predictive in diagnostic models, while co-morbidities, sex, C-reactive protein and creatinine are frequent prognostic factors [4][5][6][7][8][9][10]. With more than 90% of deaths occurring in patients over the age of 60 years, and a predominance of males, French data are consistent with that reported worldwide [1, [4][5][6][7][8][9].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…As above reported, these values could be underestimated for reasons depending on several factors like a stringent testing policy limited to severely affected symptomatic individuals, that excluded from testing the bulk of asymptomatic ones, shortage of testing materials in the peak of the emergency, limited access to overcrowded hospital facilities, to name just a few. Noteworthy, a higher overall mortality rate than previous years has been observed in Nembro, a little town of Lombardia region, indicative of both direct and indirect disease burden [4].…”
Section: Discussionmentioning
confidence: 86%
“…hospitals and intensive care units were overcrowded and many people may have died in their homes without testing. A recent observational study conducted on a small community in Nembro, a little town located in Lombardia, one of the most affected areas of northern Italy, reported an all-cause mortality between January and April 2020, several times higher than that recorded in the previous eight years in the same time frame [4]. Overall, Covid-19 deaths were mostly observed in males and older patients with preexisting comorbidities [5,6].…”
Section: Read Full Licensementioning
confidence: 96%